The 1955 General Election as the Ethical Foundation of Indonesian Democracy: A Normative-Historical and Islamic Political Perspective - Putri, Nirwana; Fatimah, Siti (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This research examines the dynamics of the 1955 General Election in Indonesia and Muhammad al-Ghazali’s perspective on electoral systems in the context of the modern state. The 1955 election marked a significant milestone in Indonesia’s democratic developm ent, applying a proportional electoral system with high voter participation. It successfully established an inclusive, accountable, and integrity-based electoral legal framework. Meanwhile, al-Ghazali’s thought highlights that democratic principles such as shura (consultation), justice, and public participation are compatible with Islamic values. Modern elections are viewed as a practical realization of shura in complex societies where direct deliberation is no longer feasible. The academic contribution of this study lies in affirming that democratic electoral systems can be grounded in Islamic ethical values, and that the historical experience of the 1955 election offers a relevant model for developing progressive electoral regulations. This research enriches the discourse on Islamic political thought and Indonesian electoral law within the context of inclusive and ethical democracy